(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2022)
INTRODUCTION: This research article seeks to evaluate, through the development and validation of a brief psychometric scale, the level of addiction to directed social networks present in two groups of university students, from the psychology and graphic design programs at the University of Santander, Cúcuta Campus. A descriptive quantitative methodology was applied to the instrument, performing a reliability analysis, discarding items, designing the structural model, confirmatory factor analysis, adjustment and verification of modeling. METHOD: A quantitative and descriptive approach, in turn presents a Likert scale, which gave way to the application and analysis of results of the scale applied to a total of 132 students. RESULTS: The data found in the initial and final evaluation were analyzed and compared through the SPSS program, where the level of reliability of the test could be observed according to Cronbach’s alpha of (a 0.894), thus demonstrating that it is a reliable instrument. Likewise, the test is composed of 29 items, resulting in the factorial analysis under 3 dimensions: use (9 items), frequency (13 items), and content (7 items)